Effectiveness of deep brain stimulation on refractory aggression in pediatric patients with autism and severe intellectual disability: meta-analytic review - Jorge Herrera-Pino; Juancarlos Benedetti-Isaac; Daniela Ripoll-Córdoba; Loida Camargo; Edgard E. Castillo-Tamara; Breiner Morales-Asencio; Esther Perea-Castro; Martín Torres Zambrano; Alejandro Ducassou; Yuliana Flórez; María F. Porto; Pascual A. Gargiulo; et al. (BMC, 2024)
Abstract Some patients with autism and severe intellectual disability may experience uncontrolled aggression, causing serious injury or harm to others, and the therapeutic ineffectiveness of traditional pharmacological and behavioral treatment may aggravate symptoms. Deep brain stimulation (DBS) has been tested in patients with little evidence in children and adolescents. Therefore, we analyzed the efficacy and safety of DBS in refractory aggression in pediatric subjects with autism (ASD) and severe intelligence deficit (ID). Methods A meta-analytic review of Web of Science (WOS) and Scopus articles, following Prisma criteria. A total of 555 articles were identified, but after applying the inclusion criteria, only 18 were analyzed. The review of the registries and the extraction of information was performed by 2 independent groups, to reduce the evaluator's bias. For the description of the results, pediatric patients with ASD or ID present in each registry, with an application of specialized scales (Overt aggression scale, OAS, and THE modified version of the OAS, MOAS) pre and post-DBS, with a clinical follow-up of at least 12 months, were considered valid. Clinical improvement was calculated using tests of aggressiveness. In each registry with available data and then pooling the means of all patients in the OAS and MOAS, the effect size of DBS (overall and per study) was estimated. Finally, the adapted NOS scale was applied to rate the studies' quality and level of bias. Results In the studies analyzed, 65/100 were pediatric patients, with a mean age of 16.8 years. Most of the studies were conducted in South America and Europe. In all teams, aggressive behavior was intractable, but only 9 groups (53/65) applied specialized scales to measure aggressiveness, and of these, only 51 subjects had a follow-up of at least 12 months. Thus, in 48/51 a clinical improvement of patients was estimated (94.2%), with a considerable overall effect size (OAS: d = 4.32; MOAS: d = 1.46). However, adverse effects and complications were found in 13/65 subjects undergoing DBS. The brain target with the most evidence and the fewest side effects was the posteromedial hypothalamic nuclei (pHypN). Finally, applying the adapted NOS scale, quality, and bias, only 9 studies show the best indicators. Conclusion An optimal level of efficacy was found in only half of the publications. This is mainly due to design errors and irrelevant information in the reports. We believe that DBS in intractable aggressiveness in children and adolescents with ASD and severe ID can be safe and effective if working groups apply rigorous criteria for patient selection, interdisciplinary assessments, objective scales for aggressiveness, and known surgical targets.